Design, Synthesis, and In vitro Anti-cervical Cancer Activity of a Novel MDM2-p53 Inhibitor Based on a Chalcone Scaffold - Alimujiang, Yusupuwajimu; Maimaiti, Aikebaier; Ablise, Mourboul; Yang, Zheng; Liu, Zhengye; Wang, Yu; Mutalipu, Zuohelaguli; Yan, Tong (Anti-Cancer Agents in Medicinal Chemistry, 2024)
Objective Several novel fluorinated chalcone derivatives were synthesized, and their in vitro anti-cervical cancer activity and mechanism of action were investigated using the parent nucleus of licorice chalcone as the lead compound backbone and MDM2-p53 as the target. Methods In this study, 16 novel chalcone derivatives (3a–3r) were designed and synthesized by molecular docking technology based on the licorice chalcone parent nucleus as the lead compound scaffold and the cancer apoptosis regulatory target MDM2–p53. The structures of these compounds were confirmed by 1H-NMR, 13C-NMR, and HR-ESI-MS. The inhibitory effects of the compounds on the proliferation of three human cervical cancer cell lines (SiHa, HeLa, and C-33A) and two normal cell lines (H8 and HaCaT) were determined by MTT assay, and the initialstructure–activity relationship was analyzed. Transwell and flow cytometry were used to evaluate the effects of target compounds on the inhibition of cancer cell migration and invasion, apoptosis induction, and cell cycle arrest. Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot (WB) were used to detect the effects of candidate compounds on mRNA, p53, and Murine double minute 2 (MDM2) protein expression. The binding characteristics of the target compounds to the MDM2 protein target in the p53–MDM2 pathway were evaluated by molecular docking technology. Results The target compounds had considerable inhibitory activity on the proliferation of three cervical cancer cell lines. Among them, compound 3k (E)-3-(4-(dimethylamino)phenyl)-2-methyl-1-(3-(trifluoromethyl)phenyl) prop-2-en-1-one) showed the highest activity against HeLa cells (IC50=1.08 μmol/L), which was better than that of the lead compound Licochalcone B, and 3k showed lower toxicity to both normal cells. Compound 3k strongly inhibited the migration and invasion of HeLa cells and induced apoptosis and cell cycle arrest at the G0/G1 phase. Furthermore, compound 3k upregulated the expression of p53 and BAX and downregulated the expression of MDM2, MDMX, and BCL2. Moreover, molecular docking results showed that compound 3k could effectively bind to the MDM2 protein (binding energy: −9.0 kcal/mol). These results suggest that the compounds may activate the p53 signaling pathway by inhibiting MDM2 protein, which prevents cancer cell proliferation, migration, and invasion and induces apoptosis and cell cycle arrest in cancer cells. Conclusion This study provides a new effective and low-toxicity drug candidate from licochalcone derivatives for treating cervical cancer.
Keywords: antitumor activity